Effects of dietary soy isoflavones on estrogenic activity, cortisol level, health and growth in rainbow trout, Oncorhynchus mykiss. (24th January 2018) - Pastore, Maria Rita; Negrato, Elena; Poltronieri, Carlo; Barion, Giuseppe; Messina, Maria; Tulli, Francesca; Ballarin, Cristina; Maccatrozzo, Lisa; Radaelli, Giuseppe; Bertotto, Daniela
Abstract: Soy isoflavones (the phytoestrogens genistein, daidzein and glycitein) may act as estrogen receptor agonists or antagonists. The aim of this study was to examine the effect of dietary isoflavones on growth, reproduction and health in rainbow trout ( Oncorhynchus mykiss ). Rainbow trout fed three experimental diets containing different concentrations of isoflavones (0, 500 and 1, 500 ppm). Growth, estrogenic activity, plasma estradiol levels, gonadal development, state of stress and histological changes in selected tissues were evaluated at the end of 70 days. Neither growth performance nor the relative mRNA levels of Insulin Growth Factor I ( igf‐ I) in the liver were influenced by different levels of dietary isoflavones. Plasma and liver vitellogenin (VTG) protein levels and plasma 17‐β‐estradiol (E2 ) were unaffected by treatments, although the correlation between plasma levels of E2 and VTG densitometry values was significant ( p < .05). The fish gonadosomatic index (GSI) did not significantly differ among the three experimental groups but correlated with plasma VTG densitometry values ( p < .05). Plasma, muscle and fin cortisol concentrations fell within the normal welfare range and were not correlated with isoflavone levels. Histologically, the distal intestine showed a normal morphology with well‐differentiated enterocytes and in the liver hepatocytes were also normal. A supranuclear accumulation of lipid droplets in enterocytes and some lipid droplets in hepatocytes were observed in all tested groups, suggesting an impact of basal dietary lipid on transport/metabolism of fat in the fish. Overall, the present results suggest that the doses of isoflavones tested do not compromise rainbow trout reproduction, growth and health.